What is cybersecurity? (O'Reilly, 2018)
"Creating and implementing an effective online security plan is vital in keeping a business safe, but how can the non-technical business manager participate in such planning without the language and understanding required to do so? In this course, Emmanuel Henri explores the basics of cybersecurity from a layman's perspective. He discusses what cybersecurity is and why it's important; he details the conversations managers must have with their teams to set the proper security initiatives and hire the proper staff; he explores the cybersecurity resources managers can easily tap into; and finishes by demonstrating the ways cybersecurity measures are applied in real life."--Resource description page